A Pilot Study of a Behavioral Parent Training in the Republic of Macedonia - Hansen, Blake D; Orton, Emma Lucy; Adams, Chase; Knecht, Laura; Rindlisbaker, Sophie; Jurtoski, Filip; Trajkovski, Vladimir (Springer Nature, 2017)
Parenting children with autism in countries with limited professional and financial resources can be overwhelming. Parent training led by non-governmental organizations may help alleviate some of these burdens. The present pilot study was conducted in the Republic of Macedonia, a country located in Southeastern Europe. The purpose of the study was to evaluate a parent training model for disseminating evidence-based practices through didactic and pyramidal training strategies. Results indicated that children improved on a number of different behaviors and results provide some evidence that parenting confidence and distress improved.
Keywords: Behavioral parent training · International settings · Behavior analysis